A potência didática das escrevivências no trabalho com os migrantes de crise - Novas, Christiane Rocha (2024)
This research aimed to investigate and analyze activities that mobilize experiential heritage (Megale; Liberali, 2020) with a group of students from the Integrated Center for Youth and Adult Education (CIEJA) Perus I, based on writing-living (Evaristo, 2003), based on memories of migrants, through work with Engaged Multiliteracy (Liberali, 2022). Throughout the first half of 2022, a group of researchers from PUC-SP visited places where migrants worked and studied and established conversations with these subjects. Getting in touch with this reality was fundamental for the researchers, in partnership with CIEJA Perus I, to prepare a meeting of the Extension and Research Project Brincadas – organized by the research group Language in Activities in the School Context (LACE) of PUC-SP – developed for and with students from this school, with mobilizing activities that were based on the narratives of these migrants. The method of this study was based on the Critical Research of Collaboration (PCCol) (Magalhães, 2009), whose corpus was analyzed from the qualitative-interpretative approach, in proposals to transform those involved. The theoretical foundation of this work was anchored in the following pillars: Writing-living, Decoloniality, Interculturality, Crisis Migrations, Engaged Multiliteracy, and Experiential Heritage. For data collection and selection, the transcription of the dialogues of the event was carried out, obtained from the data collected by the analysis of recordings, which composed 180 minutes of content in addition to planning records. Data analysis was carried out based on the actions of critical reflection (Liberali, 2018; Smyth, 1992): describe, inform, confront, and reconstruct and multimodal interpretation (Kress, 2010). The results demonstrated that working with writing-living, by giving visibility to migrants' memories, has significant potential for expanding experiential heritage. This process stood out when participants shared their personal experiences, creating an environment of profound exchanges that transcend linguistic barriers. This expansion of heritage strengthens critical awareness in situations of injustice involving migrants and other minority groups, promoting positive changes in society